Understanding The Canadian Foreign Policy Ratified Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) in 2018 - Faturachman Alputra S; Syastri Wulandari (Universitas Halu Oleo, 2019)
In 2018, Canada decided to ratify one of the Free Trade Agreement in AsiaPacific Region, it was the Comprehensive and Progressive Agreement for Trans-PacificPartnership (CPTPP). This study aims to analyse Canadian policy to join in the CPTPP useNeoliberalism approach by Balaam & Veseth (2005) to see the benefits gained from the freetrade agreement. As well as the national interest concept from Nuechterlein (1976) toanalyse the interests of Canada in ratified CPTPP in 2018. This research method usesqualitative descriptive, where data was collected through interviews and documentation.The results of this study conclude that the policy to ratified the agreement based oneconomic interests where Canada can diversify export markets, achieve tariff eliminationand market expansion.